Mica tape-SiO2 aerogel cable fire-resistant composite material and preparation method thereof, and cable containing mica tape-SiO2 aerogel cable fire-resistant composite material

By filling SiO2 aerogel into the pores of the mica belt, forming a mica belt-SiO2 aerogel composite material, the problem of insufficient fire resistance performance of existing mica belt refractory cables is solved, and the fire resistance temperature and time are significantly improved.

CN119591115APending Publication Date: 2025-03-11LANZHOU UNIVERSITY OF TECHNOLOGY
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411890236.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

The existing mica refractory cables have insufficient fire resistance, and the fire resistance temperature and time are not enough to meet the refractory needs of the cable.

Method used

Using mica belt and SiO2 aerogel composite material, a gel composite material of mica belt and SiO2 sol is prepared and processed under supercritical conditions to form a high-performance SiO2 aerogel, which is filled in the pores of mica belt.

Benefits of technology

The refractory performance of the cable is significantly improved, the refractory temperature can be increased by 200℃-300℃, and the thermal conductivity of the material is reduced at high temperatures and the refractory time is extended.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119591115A_ABST
    Figure CN119591115A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of electric engineering cables, and discloses a preparation method of a mica tape-SiO2 aerogel cable fire-resistant composite material and a cable containing the material to solve the problem that a mica tape fire-resistant layer of an existing cable is insufficient in fire resistance, and the method comprises the steps of preparing a mica tape and SiO2 sol, preparing the mica tape-SiO2 aerogel composite material and the like. According to the mica tape-SiO2 aerogel cable fire-resistant composite material produced by the invention, the fire resistance is far better than that of a common cable fire-resistant mica tape, and the fire-resistant temperature can be increased by 200-300 DEG C. The mica tape-SiO2 aerogel composite material has excellent basic electrical properties and mechanical properties, and can be applied to low-voltage fire-resistant cables. The preparation method of the mica ribbon-SiO2 aerogel composite material is simple, convenient and controllable, the SiO2 aerogel and the mica tape are good in compatibility, the SiO2 aerogel can be well attached into pores of the mica tape, and the fire resistance is stable.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of electrical engineering cables, and in particular to a method for preparing a mica tape-SiO2 aerogel cable fire-resistant composite material and a cable containing the material. Background Art

[0002] In recent years, fire accidents have occurred frequently in my country, and the fire scenes are shocking, posing a major threat to public safety and the lives and property of the people. According to statistics, electrical fires account for 33% of fire accidents in my country, and wire and cable fires account for 60% of electrical fires. How to control and reduce wire and cable fires has become an important issue facing fire prevention and control. Mica tape fire-resistant cable is currently the mainstream fire-resistant cable in China and is widely used in general firefighting occasions. Mica tape fire-resistant cable usually wraps mica tape around the cable core as a fire-resistant layer. However, at present, mica tape fire-resistant cables generally have low fire resistance grades (600℃-800℃) and short fire resistance time, which cannot meet the fire resistance requirements of cables well. How to improve the fire resistance performance of mica tape is an urgent problem to be solved.

[0003] The patent with application number CN202011445554.4 proposes an improved highly flame-retardant structural controlled fire-resistant cable, which is wrapped with a double layer of mica tape. At the same time, the sheath adopts a highly flame-retardant, low-smoke, halogen-free polyolefin sheath, which enhances the fire retardant effect of the cable.

[0004] Patent application number CN201310447884.0 discloses a mica tape for Class A fire-resistant cables, comprising a mica paper layer, a first glass cloth layer, a second glass cloth layer, a first adhesive layer and a second adhesive layer, wherein the mica paper layer is made of fluorine-gold synthetic mica. The mica tape has excellent mechanical properties, electrical properties and fire resistance.

[0005] Patent application number CN201610783046.4 discloses a high-performance flexible fire-resistant cable, which includes a conductor, and the conductor is coated with a mica tape fire-resistant layer, a special polymer material insulation layer, an aluminum foil mica paper layer, and an outer sheath layer from the inside to the outside. The fire resistance of the cable is improved by a multi-layer fire-resistant structure.

[0006] However, current mica tape fire-resistant cables usually use mica tapes with good fire resistance (such as phlogopite mica tapes or synthetic mica tapes) or design multiple fire-resistant layers to improve the fire resistance of the cable. There is no technology that improves the fire resistance of the mica tape by changing its own structure or material. Summary of the invention

[0007] The invention aims to solve the problem that the fire-resistant performance of the existing cable mica tape fire-resistant layer is insufficient, and provides a mica tape-SiO2 aerogel cable fire-resistant composite material.

[0008] In order to achieve the above object, the present invention adopts the following technical solutions: A method for preparing a mica tape-SiO2 aerogel cable fire-resistant composite material, comprising the following steps: Step 1, preparing mica tape and SiO2 sol; Step 2, after spreading the mica tape in the mold, pouring the SiO2 sol into the mold to immerse the mica tape; and letting it stand to obtain a mica tape-SiO2 gel composite material; Step 3, adding an aging solution to the mold in step 2 to immerse the mica tape-SiO2 gel composite material, and then aging it under constant temperature conditions. After the aging is completed, anhydrous ethanol is added to the mold to replace the gel; Step 4, after adding a drying medium into the drying kettle, the mica tape-SiO2 gel composite material after the gel replacement in step 3 is placed in the drying kettle, the drying kettle is closed, and then nitrogen is filled into the drying kettle and the pressure is increased to 8MPa and then the temperature is increased; Step 5, maintaining constant pressure and continuing to raise the temperature to a supercritical temperature of 270°C, maintaining constant temperature until the pressure in the drying kettle increases to a set pressure of 12 MPa, and then maintaining constant pressure; maintaining constant temperature and pressure at a supercritical temperature of 270°C and a set pressure of 12 MPa so that the ethanol in the SiO2 aerogel is completely converted into a supercritical fluid and released from the SiO2 aerogel network structure; Step 6: Open the vent valve of the drying kettle to release the supercritical fluid in the drying kettle without cooling, and the pressure in the drying kettle drops to normal pressure. Then, purge with inert gas nitrogen, and obtain the mica tape-SiO2 aerogel composite material after the temperature drops to room temperature.

[0009] In the step 1, the method for preparing the mica tape is as follows: after pouring glue into the mold, the inorganic glass fiber is arranged and soaked in the glue in the mold, taken out and drained, and laminated with mica paper to obtain a mica tape semi-finished product, and then the mica tape semi-finished product is glued on one side of the glass fiber cloth and then baked and cooled to obtain the mica tape; the glue includes organic silica gel, isopropyl alcohol and curing agent; the mass ratio of the organic silica gel to the isopropyl alcohol agent and the curing agent is 1:2:0.1; the viscosity of the organic silica gel is 450000-600000mPa.s, and the solid content is 58-62%.

[0010] In the step 1, the method for preparing SiO2 sol is: ethanol and HCl are prepared as an acid catalyst, and concentrated ammonia water and ethanol are prepared as a base catalyst; at room temperature, tetraethyl orthosilicate (TES), H2O, and ethanol (ethanol) are stirred and fully mixed in a certain proportion to form a mixed solution, an acidic catalyst is first added to adjust the pH value of the mixed solution to acidity, and after stirring for a period of time, a base catalyst is added to adjust the pH value of the mixed solution to alkalinity, and the mixed solution is continued to be stirred to finally obtain SiO2 sol; the nH2O:nTES is 2-4, and the nethanol:nTES is 9-30, wherein n is the molar mass.

[0011] An acidic catalyst was added to adjust the pH value of the mixed solution to 6-6.5, and an alkaline catalyst was added after stirring for a period of time to adjust the pH value of the mixed solution to 7.5-8; the acid-base catalytic hydrolysis temperature was 50° C., and the acid-base catalytic time was 1 hour.

[0012] In the step 2, after the mica tape is spread in the mold, SiO2 sol is poured in to immerse the mica tape; after standing for 4-12 hours, a mica tape-SiO2 gel composite material is obtained.

[0013] In the step 3, the aging solution is prepared by mixing anhydrous ethanol and tetraethyl orthosilicate in a volume ratio of 2:1. The aging solution is poured into the mold to immerse the mica tape-SiO2 gel composite material, and the composite material is allowed to stand for 48 hours at a constant temperature of 40°C for aging. After that, the aging solution is poured out, and anhydrous ethanol is added to the mold to immerse the composite material for replacement. The immersion and replacement are carried out at a constant temperature of 60°C for 3 times, each time for 24 hours.

[0014] In step 4, the drying medium added to the drying kettle is ethanol, and the amount of ethanol added is 400 mL.

[0015] In step 5, the temperature and pressure are maintained at a supercritical temperature of 270° C. and a set pressure of 12 MPa for 2-3 hours.

[0016] The beneficial effects of the present invention are as follows: 1. The mica tape-SiO2 aerogel cable fire-resistant composite material produced by the present invention has a fire-resistant performance far superior to that of ordinary cable fire-resistant mica tape, and the fire-resistant temperature can be increased by 200°C-300°C.

[0017] 2. In the mica tape-SiO2 aerogel composite material, SiO2 aerogel can fill the pores of the mica tape. Its high-temperature phase structure is stable and can significantly reduce the high-temperature thermal conductivity of the mica tape. At the same time, the mica tape contains infrared shading agents such as Al2O3, which can effectively shield high-temperature infrared radiation, inhibit the temperature rise of the material, maintain the stability of SiO2 aerogel, and improve the refractory temperature and refractory time of the composite material.

[0018] 3. Mica tape-SiO2 aerogel composite materials have excellent basic electrical and mechanical properties and can be used in low-voltage fire-resistant cables.

[0019] 4. The preparation method of mica tape-SiO2 aerogel composite material is simple and controllable. The SiO2 aerogel prepared by the acid-base two-step method has a uniform three-dimensional network structure and high mechanical strength. In addition, SiO2 aerogel and mica tape have good compatibility, can be well attached to the pores of mica tape, and has stable fire resistance.

[0020] 5. Mica tape-SiO2 aerogel composite material is composited with mica tape and SiO2 aerogel. The preparation process of mica tape and SiO2 aerogel is mature, which is convenient for industrial application and promotion. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 Microscope observation pictures of samples corresponding to mica tape and mica tape-SiO2 aerogel (formula 1) composite materials; Figure 2 Microscope observation pictures of mica tape and mica tape-SiO2 aerogel (formula 1) composite material samples after high temperature breakdown test; Figure 3 Microscope observation pictures of mica tape and mica tape-SiO2 aerogel composite material (formula 2) samples; Figure 4 Microscope observation pictures of mica tape and mica tape-SiO2 aerogel (formula 2) composite material samples after high temperature breakdown test; Figure 5 Microscope observation pictures of mica tape and mica tape-SiO2 aerogel (formula 3) composite material samples; Figure 6 Microscope observation pictures of mica tape and mica tape-SiO2 aerogel (formula 3) composite material samples after high-temperature breakdown experiment. DETAILED DESCRIPTION

[0022] A method for preparing a mica tape-SiO2 aerogel cable fire-resistant composite material comprises the following steps: Step 1, preparing mica tape and SiO2 sol; The mica tape preparation method is as follows: a groove-shaped stainless steel mold is made, and the size of the stainless steel mold is 1000mm×500mm×50mm; glue is poured into the mold, and the glue includes organic silica gel, solvent and curing agent. In the glue, the mass ratio of organic silica gel to solvent is 1:2:0.1; the solvent is isopropyl alcohol; the viscosity of the organic silica gel is 450000-600000mPa.s, and the solid content is 58-62%; inorganic glass fiber matching the shape of the inner groove of the stainless steel mold is arranged in the stainless steel mold and soaked in glue for 5 minutes, taken out and drained, and then bonded with mica paper to obtain a mica tape semi-finished product, and a gluing device is used to perform glue repair on one side of the glass fiber cloth of the mica tape semi-finished product twice, and the semi-finished product is placed in a multi-stage drying box for baking and cooling to obtain a mica tape; the inorganic glass fiber cloth has a low apparent density, a certain toughness and mechanical strength, high temperature resistance, and good compatibility with SiO2 aerogel, and is suitable as a cable fireproof material. In addition, the porosity of inorganic glass fiber cloth is 90-95%. When it is mixed with SiO2 sol, the sol can completely penetrate into the micron-level and millimeter-level gaps of the glass fiber cloth and fully infiltrate most of the fibers, reducing the contact between each fiber, thereby improving the fire resistance of the composite material.

[0023] The preparation method of SiO2 sol is as follows: dilute HCl with ethanol as an acid catalyst, and use concentrated ammonia water and ethanol as a base catalyst; mix tetraethyl orthosilicate, H2O, and ethanol at a certain molar mass ratio (nH2O:n tetraethyl orthosilicate is 2-4, nethanol:n tetraethyl orthosilicate is 9-30, wherein n is the molar mass) at room temperature and stir thoroughly, then add an acid catalyst to adjust the pH value of the mixed solution to 6-6.5, at which time the gelation time is short and it is not easy to cause SiO2 particle deposition; magnetically stir the mixed solution at 50°C for 1 hour, then add ammonia water to the mixed solution to adjust its pH value to 7.5-8, at which time the polymerization reaction is relatively stable, which is conducive to the formation of a gel nano-network structure, and obtains a SiO2 aerogel with low density and high network skeleton structure strength; magnetically stir the mixed solution at 50°C for 1 hour to obtain SiO2 sol; in acid catalysis, the hydrolysis rate of tetraethyl orthosilicate is greater than the condensation rate, which is conducive to the nucleation reaction and produces many sol monomers. In alkaline catalysis, the polycondensation reaction rate of tetraethyl orthosilicate is greater than the hydrolysis rate, and the sol monomer grows and cross-links, thereby preparing a SiO2 sol with a long-chain cross-linked structure and high skeleton strength.

[0024] Step 2, after spreading the mica tape in the mold, pouring the SiO2 sol into it to immerse the mica tape; after standing for 4-12 hours, a mica tape-SiO2 gel composite material is obtained; Step 3, anhydrous ethanol and tetraethyl orthosilicate are prepared into an aging solution in a volume ratio of 2:1, and the aging solution is added to the mold in step 2 to immerse the mica tape-SiO2 gel composite material, and then it is aged for 48 hours at a constant temperature of 40°C. After the mica tape-SiO2 gel composite material is aged, the unreacted silicon alcohol salt will continue to react with tetraethyl orthosilicate, so that the alcohol gel network structure is strengthened and the hardness is increased. At the same time, the -OH on the alcohol gel SiO2 network reacts with ethanol to make part of the -OH groups react to become -OR. During the drying process, adjacent -OH will not react with each other, and the shrinkage of the wet gel after drying is reduced accordingly. The aging temperature is selected as 40°C to accelerate the aging rate without destroying the SiO2 gel structure; after the aging is completed, the aging solution is poured out, and anhydrous ethanol is added to the mold to immerse the mica tape-SiO2 gel composite material for gel replacement; soak and replace 3 times at a constant temperature of 60°C, each time for 24 hours.

[0025] Step 4, ethanol is added as a drying medium in the drying kettle, and the amount of ethanol added is 400 mL. After the drying medium is added to the drying kettle, the mica tape-SiO2 gel composite material after the gel replacement in step 3 is placed in the drying kettle, the drying kettle is closed, and then nitrogen is filled into the drying kettle and the pressure is increased to 8MPa and then the temperature is increased. The aerogel obtained by supercritical drying of ethanol shrinks less and part of the -OH on the surface is changed to -OR. The aerogel obtained in this way has certain hydrophobicity and a stable nanostructure.

[0026] Step 5: Keep constant pressure and continue to raise the temperature to the supercritical temperature of 270°C. Keep constant temperature until the pressure in the drying kettle increases to the set pressure of 12MPa, and then keep constant pressure. Keep constant temperature and pressure at the supercritical temperature (270°C) and set pressure (12MPa) for 2-3 hours, so that the ethanol in the SiO2 aerogel is completely converted into a supercritical fluid and released from the SiO2 aerogel network structure.

[0027] Step 6: Open the vent valve of the drying kettle to release the supercritical fluid in the drying kettle without cooling, and the pressure in the drying kettle drops to normal pressure. Then, purge with inert gas nitrogen, and obtain the mica tape-SiO2 aerogel composite material after the temperature drops to room temperature. Example 1

[0028] A method for preparing a mica tape-SiO2 aerogel cable fire-resistant composite material comprises the following steps: Step 1, preparing mica tape and SiO2 sol; The mica tape preparation method is as follows: a groove-shaped stainless steel mold is made, and the size of the stainless steel mold is 1000mm×500mm×50mm; glue is poured into the mold, and the glue includes organic silica gel, solvent and curing agent. In the glue, the mass ratio of organic silica gel, solvent and curing agent is 1:2:0.1; the solvent is isopropyl alcohol; the viscosity of the organic silica gel is 450000-600000mPa.s, and the solid content is 58-62%; inorganic glass fiber matching the shape of the inner groove of the stainless steel mold is arranged in the stainless steel mold and soaked in glue for 5 minutes, taken out and drained, and then bonded with mica paper to obtain a mica tape semi-finished product, and a gluing device is used to perform glue repair on the mica tape semi-finished product twice on one side of the glass fiber cloth, and the semi-finished product is placed in a multi-stage drying box for baking and cooling to obtain a mica tape.

[0029] The preparation method of SiO2 sol is as follows: dilute HCl with ethanol as an acid catalyst, and use concentrated ammonia water and ethanol as a base catalyst; mix tetraethyl orthosilicate, H2O, and ethanol at a ratio of n tetraethyl orthosilicate: nH2O: n ethanol of 1:2:9 and stir thoroughly at room temperature, and after stirring, add an acid catalyst to adjust the pH value of the mixed solution to 6, at which time the gel time is short and it is not easy to cause SiO2 particle deposition; magnetically stir the mixed solution at 50°C for 1 hour, and then add ammonia water to the mixed solution to adjust its pH value to 7.5, at which time the polymerization reaction is relatively stable, which is conducive to the formation of a gel nano-network structure, and obtain a SiO2 aerogel with low density and high network skeleton structure strength; magnetically stir the mixed solution at 50°C for 1 hour to obtain SiO2 sol.

[0030] Step 2, after laying the mica tape in the mold, pouring the SiO2 sol into it to immerse the mica tape; after standing for 4-12 hours, a mica tape-SiO2 gel composite material is obtained; Step 3: prepare an aging solution by mixing ethanol and tetraethyl orthosilicate in a volume ratio of 2:1, add the aging solution to the mold in step 2 to immerse the mica tape-SiO2 gel composite material, and then place it at a constant temperature of 40°C for 48 hours for aging. The aging temperature is selected to be 40°C in order to accelerate the aging rate without destroying the SiO2 gel structure; after the aging is completed, pour out the aging solution, add anhydrous ethanol to the mold to immerse the mica tape-SiO2 gel composite material for gel replacement; soak and replace it at a constant temperature of 60°C for 3 times, each time for 24 hours.

[0031] Step 4: Add ethanol as a drying medium into the drying kettle, and the amount of ethanol added is 400 mL. After the drying medium is added into the drying kettle, the mica tape-SiO2 gel composite material after the gel replacement in step 3 is placed into the drying kettle, the drying kettle is closed, and then nitrogen is filled into the drying kettle and the pressure is increased to 8 MPa and then the temperature is increased.

[0032] Step 5: Keep constant pressure and continue to raise the temperature to the supercritical temperature of 270°C. Keep constant temperature until the pressure in the drying kettle increases to the set pressure of 12MPa, and then keep constant pressure. Keep constant temperature and pressure at the supercritical temperature (270°C) and set pressure (12MPa) for 2-3 hours, so that the ethanol in the SiO2 aerogel is completely converted into a supercritical fluid and released from the SiO2 aerogel network structure.

[0033] Step 6: Open the vent valve of the drying kettle to release the supercritical fluid in the drying kettle without cooling, and the pressure in the drying kettle drops to normal pressure. Then, purge with inert gas nitrogen, and obtain the mica tape-SiO2 aerogel composite material after the temperature drops to room temperature.

[0034] Microscopic observation, before the combustion experiment, two samples of mica tape and mica tape-SiO2 aerogel (formula 1) composite material were microscopically observed. The observation results are as follows: Figure 1 Obvious horizontal and vertical glass fiber stripes can be observed in both samples.

[0035] In the combustion experiment (high temperature and pressure combustion experiment), the two samples were wrapped around a copper rod with a length of 20 cm and a diameter of 1 cm, and the copper wire was wrapped around the outside of the sample, and then the sample was placed in a muffle furnace. A 50 V AC voltage was applied to the copper rod and the copper wire was grounded (the equivalent field strength on the mica tape was 0.04 kV / mm) to simulate the voltage on the mica tape when the low-voltage cable burned. The temperature of the muffle furnace was raised from 20°C to 1000°C at a heating rate of 16.3°C / min and then kept constant to simulate the burning of the low-voltage cable. The breakdown temperature and breakdown time of the samples were recorded, and the statistical results are shown in Table 1. The average breakdown temperature of the mica tape-SiO2 aerogel (formula 1) composite material sample was 215°C higher than that of the mica tape sample, and the average breakdown time of the mica tape-SiO2 aerogel (formula 1) composite material sample was higher than that of the mica tape sample.

[0036] The combustion samples were observed under microscope. Figure 2 As shown. Figure 2 It can be seen that the glass fiber on the mica tape sample has been ablated, narrowed, and deformed, and there are obvious ablation holes, while the glass fiber of the mica tape-SiO2 aerogel (Formula 1) composite material sample is still intact, indicating that the fire resistance of the mica tape-SiO2 aerogel (Formula 1) composite material sample is better than that of the mica tape sample.

[0037] Table 1 Statistical results of breakdown temperature and breakdown time of samples Example 2

[0038] A method for preparing a mica tape-SiO2 aerogel cable fire-resistant composite material comprises the following steps: Step 1, preparing mica tape and SiO2 sol; The mica tape preparation method is as follows: a groove-shaped stainless steel mold is made, and the size of the stainless steel mold is 1000mm×500mm×50mm; glue is poured into the mold, and the glue includes organic silica gel, solvent and curing agent. In the glue, the mass ratio of organic silica gel, solvent and curing agent is 1:2:0.1; the viscosity of the organic silica gel is 450000-600000mPa.s, and the solid content is 58-62%; inorganic glass fiber matching the shape of the inner groove of the stainless steel mold is arranged in the stainless steel mold and soaked in glue for 5 minutes, taken out and drained, and then bonded with mica paper to obtain a mica tape semi-finished product, and a gluing device is used to perform glue repair on the mica tape semi-finished product twice on one side of the glass fiber cloth, and the semi-finished product is placed in a multi-stage drying box for baking and cooling to obtain a mica tape;.

[0039] The preparation method of SiO2 sol is as follows: HCl is diluted with ethanol as an acid catalyst, and concentrated ammonia water and ethanol are used as a base catalyst; at room temperature, tetraethyl orthosilicate, H2O, and ethanol are prepared into a mixed solution in a ratio of n tetraethyl orthosilicate: nH2O: nethanol of 1:3:15, and after sufficient mixing and stirring, an acid catalyst is added to adjust the pH value of the mixed solution to 6.3, at which time the gelation time is short and it is not easy to cause SiO2 particle deposition; the mixed solution is magnetically stirred at 50°C for 1 hour, and then ammonia water is added to the mixed solution to adjust its pH value to 7.8, at which time the polymerization reaction is relatively stable, which is conducive to the formation of a gel nano-network structure, and a SiO2 aerogel with low density and high network skeleton structure strength is obtained; the mixed solution is magnetically stirred at 50°C for 1 hour to obtain SiO2 sol.

[0040] Step 2, after spreading the mica tape in the mold, pouring the SiO2 sol into it to immerse the mica tape; after standing for 4-12 hours, a mica tape-SiO2 gel composite material is obtained; Step 3: prepare an aging solution by mixing ethanol and tetraethyl orthosilicate in a volume ratio of 2:1, add the aging solution to the mold in step 2 to immerse the mica tape-SiO2 gel composite material, and then place it at a constant temperature of 40°C for 48 hours for aging. The aging temperature is selected to be 40°C in order to accelerate the aging rate without destroying the SiO2 gel structure; after the aging is completed, pour out the aging solution, add anhydrous ethanol to the mold to immerse the mica tape-SiO2 gel composite material for gel replacement; soak and replace it at a constant temperature of 60°C for 3 times, each time for 24 hours.

[0041] Step 4: Add ethanol as a drying medium into the drying kettle, and the amount of ethanol added is 400 mL. After the drying medium is added into the drying kettle, the mica tape-SiO2 gel composite material after the gel replacement in step 3 is placed into the drying kettle, the drying kettle is closed, and then nitrogen is filled into the drying kettle and the pressure is increased to 8 MPa and then the temperature is increased.

[0042] Step 5: Keep constant pressure and continue to raise the temperature to the supercritical temperature of 270°C. Keep constant temperature until the pressure in the drying kettle increases to the set pressure of 12MPa, and then keep constant pressure. Keep constant temperature and pressure at the supercritical temperature (270°C) and set pressure (12MPa) for 2-3 hours, so that the ethanol in the SiO2 aerogel is completely converted into a supercritical fluid and released from the SiO2 aerogel network structure.

[0043] Step 6: Open the vent valve of the drying kettle to release the supercritical fluid in the drying kettle without cooling, and the pressure in the drying kettle drops to normal pressure. Then, purge with inert gas nitrogen, and obtain the mica tape-SiO2 aerogel composite material after the temperature drops to room temperature.

[0044] Microscopic observation. Before the combustion experiment, microscopic observations were performed on two samples of mica tape and mica tape-SiO2 aerogel (formula 2) composite material. The observation results are shown in the figure. Figure 3 Obvious horizontal and vertical glass fiber stripes can be observed in both samples.

[0045] Combustion experiment (high temperature and pressure combustion experiment). The two samples were wrapped around a copper rod with a length of 20 cm and a diameter of 1 cm, and the copper wire was wrapped around the outside of the sample, and then the sample was placed in a muffle furnace. A 50 V AC voltage was applied to the copper rod and the copper wire was grounded (the equivalent field strength on the mica tape was 0.04 kV / mm) to simulate the voltage on the mica tape when the low-voltage cable burned. The temperature of the muffle furnace was raised from 20°C to 1000°C at a heating rate of 16.3°C / min and then kept constant to simulate the burning of the low-voltage cable. The breakdown temperature and breakdown time of the samples were recorded, and the statistical results are shown in Table 2. The average breakdown temperature of the mica tape-SiO2 aerogel (formula 2) composite material sample was 243°C higher than that of the mica tape sample, and the average breakdown time of the mica tape-SiO2 aerogel (formula 2) composite material sample was higher than that of the mica tape sample.

[0046] Table 2 Statistical results of breakdown temperature and breakdown time of samples

[0047] The combustion samples were observed under microscope. Figure 4 As shown. Figure 4 It can be seen that the glass fiber on the mica tape sample has been ablated, narrowed and broken, while the glass fiber of the mica tape-SiO2 aerogel (Formula 2) composite material sample is still intact, indicating that the fire resistance of the mica tape-SiO2 aerogel (Formula 2) composite material sample is better than that of the mica tape sample. Example 3

[0048] A method for preparing a mica tape-SiO2 aerogel cable fire-resistant composite material comprises the following steps: Step 1, preparing mica tape and SiO2 sol; The mica tape preparation method is as follows: a groove-shaped stainless steel mold is made, and the size of the stainless steel mold is 1000mm×500mm×50mm; glue is poured into the mold, and the glue includes organic silica gel, solvent and curing agent. In the glue, the mass ratio of organic silica gel, solvent and curing agent is 1:2:0.1; the solvent is isopropyl alcohol; the viscosity of the organic silica gel is 450000-600000mPa.s, and the solid content is 58-62%; inorganic glass fiber matching the shape of the inner groove of the stainless steel mold is arranged in the stainless steel mold and soaked in glue for 5 minutes, taken out and drained, and then bonded with mica paper to obtain a mica tape semi-finished product, and a gluing device is used to perform glue repair on the mica tape semi-finished product twice on one side of the glass fiber cloth, and the semi-finished product is placed in a multi-stage drying box for baking and cooling to obtain a mica tape.

[0049] The preparation method of SiO2 sol is as follows: HCl is diluted with ethanol as an acid catalyst, and concentrated ammonia water and ethanol are used as a base catalyst; at room temperature, tetraethyl orthosilicate, H2O, and ethanol are prepared into a mixed solution in a ratio of n tetraethyl orthosilicate: nH2O: n ethanol of 1:4:30, and after sufficient mixing and stirring, an acid catalyst is added to adjust the pH value of the mixed solution to 6.5, at which time the gel time is short and it is not easy to cause SiO2 particle deposition; the mixed solution is magnetically stirred at 50°C for 1 hour, and then ammonia water is added to the mixed solution to adjust its pH value to 8, at which time the polymerization reaction is relatively stable, which is conducive to the formation of a gel nano-network structure, and a SiO2 aerogel with low density and high network skeleton structure strength is obtained; the mixed solution is magnetically stirred at 50°C for 1 hour to obtain SiO2 sol.

[0050] Step 2, after laying the mica tape in the mold, pouring the SiO2 sol into it to immerse the mica tape; after standing for 4-12 hours, a mica tape-SiO2 gel composite material is obtained; Step 3: prepare an aging solution by mixing ethanol and tetraethyl orthosilicate in a volume ratio of 2:1, add the aging solution to the mold in step 2 to immerse the mica tape-SiO2 gel composite material, and then place it at a constant temperature of 40°C for 48 hours for aging. The aging temperature is selected to be 40°C in order to accelerate the aging rate without destroying the SiO2 gel structure; after the aging is completed, pour out the aging solution, add anhydrous ethanol to the mold to immerse the mica tape-SiO2 gel composite material for gel replacement; soak and replace it at a constant temperature of 60°C for 3 times, each time for 24 hours.

[0051] Step 4: Add ethanol as a drying medium into the drying kettle, and the amount of ethanol added is 400 mL. After the drying medium is added into the drying kettle, the mica tape-SiO2 gel composite material after the gel replacement in step 3 is placed into the drying kettle, the drying kettle is closed, and then nitrogen is filled into the drying kettle and the pressure is increased to 8 MPa and then the temperature is increased.

[0052] Step 5: Keep constant pressure and continue to raise the temperature to the supercritical temperature of 270°C. Keep constant temperature until the pressure in the drying kettle increases to the set pressure of 12MPa, and then keep constant pressure. Keep constant temperature and pressure at the supercritical temperature (270°C) and set pressure (12MPa) for 2-3 hours, so that the ethanol in the SiO2 aerogel is completely converted into a supercritical fluid and released from the SiO2 aerogel network structure.

[0053] Step 6: Open the vent valve of the drying kettle to release the supercritical fluid in the drying kettle without cooling, and the pressure in the drying kettle drops to normal pressure. Then, purge with inert gas nitrogen, and obtain the mica tape-SiO2 aerogel composite material after the temperature drops to room temperature.

[0054] Microscopic observation. Before the combustion experiment, microscopic observations were performed on two samples of mica tape and mica tape-SiO2 aerogel (formula 3) composite material. The observation results are shown in the figure. Figure 5 Obvious horizontal and vertical glass fiber stripes can be observed in both samples.

[0055] Combustion experiment (high temperature and pressure combustion experiment). The two samples were wrapped around a copper rod with a length of 20 cm and a diameter of 1 cm, and the copper wire was wrapped around the outside of the sample, and then the sample was placed in a muffle furnace. A 50 V AC voltage was applied to the copper rod and the copper wire was grounded (the equivalent field strength on the mica tape was 0.04 kV / mm) to simulate the voltage on the mica tape when the low-voltage cable burned. The temperature of the muffle furnace was raised from 20°C to 1000°C at a heating rate of 16.3°C / min and then kept constant to simulate the burning of the low-voltage cable. The breakdown temperature and breakdown time of the samples were recorded, and the statistical results are shown in Table 3. The average breakdown temperature of the mica tape-SiO2 aerogel (formula 3) composite material sample was 224°C higher than that of the mica tape sample, and the average breakdown time of the mica tape-SiO2 aerogel (formula 3) composite material sample was higher than that of the mica tape sample.

[0056] The combustion samples were observed under microscope. Figure 6 As shown. Figure 6 It can be seen that the glass fiber on the mica tape sample has been ablated and narrowed, and there are obvious ablation holes, while the glass fiber of the mica tape-SiO2 aerogel (Formula 3) composite material sample is still intact, indicating that the fire resistance of the mica tape-SiO2 aerogel (Formula 3) composite material sample is better than that of the mica tape sample.

[0057] Table 3 Statistical results of breakdown temperature and breakdown time of samples

Claims

1. A method for preparing a mica tape-SiO2 aerogel cable refractory composite material, characterized in that: The following steps are involved: Step 1, preparing mica tape and SiO2 sol; Step 2, after spreading the mica tape in the mold, pouring the SiO2 sol into the mold to immerse the mica tape; letting it stand to obtain a mica tape-SiO2 gel composite material; Step 3, adding an aging solution to the mold in step 2 to immerse the mica tape-SiO2 gel composite material, wherein the aging solution is prepared by anhydrous ethanol and tetraethyl orthosilicate in a volume ratio of 2:1, and the composite material is allowed to stand for 48 hours at a constant temperature of 40°C for aging, then pouring out the aging solution, and adding anhydrous ethanol to the mold to immerse the composite material for replacement; Step 4, after adding the drying medium into the drying kettle, the mica tape-SiO2 gel composite material after the gel replacement in step 3 is placed into the drying kettle, the drying kettle is closed, and then nitrogen is filled into the drying kettle to increase the pressure to 8MPa and then the temperature is increased; Step 5, maintaining constant pressure and continuing to raise the temperature to a supercritical temperature of 270°C, maintaining a constant temperature of 270°C to increase the pressure in the drying kettle to a set pressure of 12MPa, and then maintaining a constant pressure; at a supercritical temperature of 270°C and a set pressure of 12MPa, the ethanol in the SiO2 aerogel is completely converted into a supercritical fluid and released from the SiO2 aerogel network structure by constant temperature and pressure; Step 6, open the vent valve of the drying kettle, release the supercritical fluid in the drying kettle without cooling, and reduce the pressure in the drying kettle to normal pressure; then purge with inert gas nitrogen, and obtain the mica tape-SiO2 aerogel composite material after the temperature drops to room temperature.

2. The method for preparing a mica tape-SiO2 aerogel cable refractory composite material according to claim 1, characterized in that: In the step 1, the method for preparing the mica tape is: after pouring glue into the mold, the inorganic glass fiber is arranged in the glue in the mold and soaked, taken out and drained, and laminated with mica paper to obtain a mica tape semi-finished product, and then the mica tape semi-finished product is glued on one side of the glass fiber cloth and then baked and cooled to obtain the mica tape; the glue includes organic silica gel, isopropyl alcohol and curing agent, and the mass ratio of organic silica gel, isopropyl alcohol agent and curing agent is 1:2:0.

1.

3. The method for preparing a mica tape-SiO2 aerogel cable refractory composite material according to claim 1, characterized in that: In the step 1, the method for preparing SiO2 sol is: at room temperature, tetraethyl orthosilicate, H2O, and ethanol are stirred and fully mixed to form a mixed solution, an acidic catalyst is first added to adjust the pH value of the mixed solution to 6-6.5, and after stirring, an alkaline catalyst is added to adjust the pH value of the mixed solution to 7.5-8, and the mixed solution is continued to be stirred to finally obtain SiO2 sol; the nH2O:n tetraethyl orthosilicate is 2-4, and the nethanol:n tetraethyl orthosilicate is 9-30, wherein n is the molar mass.

4. The method for preparing a mica tape-SiO2 aerogel cable refractory composite material according to claim 3, characterized in that: The acid-base catalytic hydrolysis temperature was 50°C, and the acid-base catalytic time was 1 h.

5. The method for preparing a mica tape-SiO2 aerogel cable refractory composite material according to claim 1, characterized in that: In the step 2, after the mica tape is spread in the mold, SiO2 sol is poured in to immerse the mica tape; after standing for 4-12 hours, a mica tape-SiO2 gel composite material is obtained; during the replacement in the step 3, the replacement is carried out at a constant temperature of 60°C for 3 times, each time for 24 hours.

6. The method for preparing a mica tape-SiO2 aerogel cable refractory composite material according to claim 2, characterized in that: The viscosity of the organic silica gel is 450000-600000 mPa.s, and the solid content is 58-62%.

7. The method for preparing a mica tape-SiO2 aerogel cable refractory composite material according to claim 1, characterized in that: In step 4, the drying medium added to the drying kettle is ethanol, and the amount of ethanol added is 400 mL.

8. The method for preparing a mica tape-SiO2 aerogel cable refractory composite material according to claim 1, characterized in that: In step 5, the temperature and pressure are maintained at a supercritical temperature of 270° C. and a set pressure of 12 MPa for 2-3 hours.

9. A mica tape-SiO2 aerogel cable fire-resistant composite material, characterized in that: A mica tape-SiO2 aerogel cable fire-resistant composite material prepared by the method for preparing a mica tape-SiO2 aerogel cable fire-resistant composite material as described in any one of claims 1 to 7.

10. A cable, characterized in that: It comprises a cable made from the mica tape-SiO2 aerogel cable fire-resistant composite material as described in claim 9.

Citation Information

Patent Citations

  • Mica tape for grade-A fire-resistant cable

    CN103481598A

  • High-performance flexible fire-resistant cable

    CN106448890A

  • Improved high-flame-retardant structure control fire-resistant cable

    CN112562890A